PERAN GAYA KEPEMIMPINAN DEMOKRATIS DALAM MENGOPTIMALKAN KINERJA PEGAWAI KEPENDIDIKAN DI MTS AL HIDAYAH SUKATANI KOTA DEPOK - Nuruliman, Mustakim; Sirajuddin (Journal of Research and Publication Innovation, 2023)
This research is entitled "The Role of Democratic Leadership Style in Optimizing the Performance of Educational Staff at MTS Al Hidayah Sukatani Depok City". This research is a qualitative research type, where the data collection method uses interviews, observation and documentation. This study aims to determine how big the role of democratic leadership style is in optimizing the performance of education staff at MTS Al Hidayah Sukatani, Depok City. As for the final results of the research that the researchers conducted during the five months of data collection, namely, the democratic leadership style played a very important role in the leadership of the MTS Al Hidayah Sukatani school principal, Depok City. The principal of MTS Al Hidayah Sukatani, Depok City, has so far been quite good at applying a democratic leadership style. This democratic leadership style is less pressing on subordinates, because it is humane and familial. In addition, the busyness of school principals outside MTS Al Hidayah Sukatani, Depok City, resulted in a lack of intensive supervision. This will have the potential for the existence of diversion of duties and responsibilities. Therefore it would be much better if the principal of MTS Al Hidayah combined this democratic leadership style with other leadership styles, but did not reduce the image of the existing democratic leadership style. So as to create a balance between comfort and work pressure in agency operations. In addition, it is hoped that the principal will spend more time at MTS Al Hidayah Sukatani, Depok City, to provide better supervision and guidance.